(untitled) (Al-Qamar, 2023)
The Holy Quran is known for its Grammatical knowledge but this aspect is often ignored or neglected. This article is an attempt to highlight this aspect. The maim object of this article is serving the holy Quran and subsiding the minded person to know the preponderant race of the verse under discussion, so in this article is being given examples from (Al-Muharrar al-Wajīz, Ibn Atiia and Al-Dur al-Masoon, Al-Sameen al-Halbi). This attempt will help the serious reader of the Holy Quran to have a deeper and fuller comprehension and appreciation of the meanings of the Holy Quran. A study of the grammatical problems makes the reading of the Holy Quran a more fascinating and beneficent experience. It also helps to catch a glimpse of the broader spectrum and profundity of the Quranic teachings.